2023
DOI: 10.1186/s12987-023-00420-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and mitochondrial changes in murine choroid plexus epithelial cells during healthy aging

Abstract: Background Choroid plexuses (ChPs) are intraventricular structures mainly composed by specialized epithelial cells interconnected by tight junctions that establish the blood-cerebrospinal fluid (CSF) barrier. ChPs are essential to produce CSF and transport solutes from and into the brain. Deterioration of ChP function and morphology has been correlated to worsening of neurodegenerative disorders. We here map morpho-functional changes in the ChP epithelial cells during healthy aging, starting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Serot et al ( Serot et al, 2000 ) found the effect of aging on epithelial flattening was exacerbated with Alzheimer’s disease. Scarpetta et al ( Scarpetta et al, 2023a ) have also recently reported reductions in microvilli height and reduced mitochondria density with aging in mice. Many CP ion transporters are energy dependent implying that the lower mitochondrial content may reduce ion transport and, thus, CSF secretion.…”
Section: Variations In Brain Fluid Secretionmentioning
confidence: 92%
See 1 more Smart Citation
“…Serot et al ( Serot et al, 2000 ) found the effect of aging on epithelial flattening was exacerbated with Alzheimer’s disease. Scarpetta et al ( Scarpetta et al, 2023a ) have also recently reported reductions in microvilli height and reduced mitochondria density with aging in mice. Many CP ion transporters are energy dependent implying that the lower mitochondrial content may reduce ion transport and, thus, CSF secretion.…”
Section: Variations In Brain Fluid Secretionmentioning
confidence: 92%
“…Changes in CSF secretion rate with age are associated with altered CP epithelial structure/function. Thus, the CP epithelium becomes flattened with a thicker basement membrane during aging in human and rodents ( Preston, 2001 ; Scarpetta et al, 2023b ; Serot et al, 2000 ). Serot et al ( Serot et al, 2000 ) found the effect of aging on epithelial flattening was exacerbated with Alzheimer’s disease.…”
Section: Variations In Brain Fluid Secretionmentioning
confidence: 99%
“…During development and aging, ChP epithelial cells undergo complex morphological transformations, including the regression of the ciliary axonemes over time, shortening of microvilli and overall cell flattening in mice. Elongation of mitochondria shape was also observed with aging [ 39 ]. Zebrafish ChP cells also undergo complex morphological transformation during development with the acquisition of a multiciliated fate [ 7 , 16 ].…”
Section: Choroid Plexus Cellular Heterogeneity: a Unique Cytoarchitec...mentioning
confidence: 99%
“…CPEs of elderly humans are known to exhibit decreases in the total volume, height, and length of apical villi, compared with cells of younger people [9,12]. Scarpetta et al [75] reported age-related changes in murine CPEs, such as flattening of epithelial cells, reduction in microvilli length, an increase in interrupted TJs, and a decrease in mitochondrial density with elongation of mitochondria [75]. These morphological mitochondrial alterations were accompanied by increased superoxide levels and a decreased membrane potential [75].…”
Section: Age-related Morphological Changes In Cpesmentioning
confidence: 99%
“…Scarpetta et al [75] reported age-related changes in murine CPEs, such as flattening of epithelial cells, reduction in microvilli length, an increase in interrupted TJs, and a decrease in mitochondrial density with elongation of mitochondria [75]. These morphological mitochondrial alterations were accompanied by increased superoxide levels and a decreased membrane potential [75]. Wakamatsu et al [33] reported that immunoreactivities for osteopontin and collagen were present in the densely fibrous or calcified CP stroma of aged human brains.…”
Section: Age-related Morphological Changes In Cpesmentioning
confidence: 99%